Determination of Drying Characteristics of Various Seafood by Freeze-drying Method and Investigation of the Effect of Ultrasonic Pretreatment - Ozyalcin, Zehra Ozden; Gules, Elif; Uygunoz, Deniz; Bozkurt, Fatih; Sagdic, Osman; Doymaz, Ibrahim; Tugrul, Nurcan; Derun, Emek; Kipcak, Azmi Seyhun (CENTRAL FISHERIES RESEARCH INST, 2024)
Freeze-drying properties, effective moisture diffusivity, mathematical modeling, and quality parameters of squid, shrimp, and mussels were investigated. Samples were evaluated as ultrasonic (US) pre-treated and untreated. Drying times were found to be 420 minutes in all samples, US pretreatment decreased the moisture content after drying and increased drying rates. The highest fit for all models was found in the Alibas model. US pretreatment caused a decrease in ash content due to the release of some minerals into the water but did not cause a significant change in protein and crude lipid amounts. US pretreatment increased the lightness of the samples.
Keywords: Freeze-drying; Mussel; Seafood; Shrimp; Squid; TEMPERATURE; KINETICS; Fisheries; Marine & Freshwater Biology